2020
DOI: 10.1016/j.jmig.2019.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Novel Minimally Invasive Technique of Neovaginoplasty Using an Absorbable Adhesion Barrier

Abstract: Our objective was to provide a minimally invasive neovaginoplasty technique to construct a nearly physiologic vagina to facilitate sexual functioning and appropriate vaginal length in patients with congenital vaginal agenesis. This retrospective study at a tertiary care hospital comprised 52 patients with congenital vaginal agenesis because of Mayer-Rokitansky-K€ uster-Hauser syndrome or androgen insensitivity syndrome presented for vaginal reconstruction. Modified McIndoe vaginoplasty was done in all patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…23 A large Indian study by Anagani et al over 8 years with 52 women with MRKH showed operative time of 35 min, and neovaginal length of average 8.4 cm, which is comparable with our study. 24 It is not only the length of neovagina that is important but the function also plays a major role in sexual satisfaction and with Interceed the epithelization takes place within 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…23 A large Indian study by Anagani et al over 8 years with 52 women with MRKH showed operative time of 35 min, and neovaginal length of average 8.4 cm, which is comparable with our study. 24 It is not only the length of neovagina that is important but the function also plays a major role in sexual satisfaction and with Interceed the epithelization takes place within 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…To solve this problem, some authors have proposed the use of molds with different dimensions or personalized molds [18,19]. Anagani et al [20] recently published data on the modification of the McIndoe technique in 52 patients in India, in which acceptable short-term physiological and psychological results and adequate epithelialization of the neovagina were achieved between 4 and 6 months. An invariable mold was used in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, amnion, peritoneum, buccal mucosa, absorbable adhesion barriers, or even tissue-engineered biomaterial mesh can be used as graft material. [28][29][30] Vaginal pull-through is also described for vaginal atresia in the pediatric population. 23,27…”
Section: Vaginal Atresia and Aplasia (Or Agenesis)mentioning
confidence: 99%